Penerapan Terapi Relaksasi Napas Dalam Dan Murottal Al- Qur’an Terhadap Penurunan Kecemasan Pada Pasien Hipertensi - Asep Riyana; Sri Rejeki Maharani; Dudi Hartono (Jurnal Kesehatan Mahardika, 2025)
Hypertension is a persistent increase in arterial blood pressure and is often accompanied by anxiety, which can hinder treatment effectiveness. Non-pharmacological interventions are needed to address these psychological issues. Deep breathing relaxation therapy and Qur’an recitation are considered effective complementary nursing strategies. This case study aims to describe the application of a combination of these two therapies and to evaluate the response of hypertensive patients to the intervention. A qualitative case study design with a comparative approach was conducted on two hypertensive patients hospitalized from April 11–16, 2025. The intervention was carried out over five consecutive days, with daily evaluation of anxiety signs and symptoms. The results showed a significant reduction in anxiety, with 11 signs and symptoms decreasing in the first patient and 15 in the second. The combination of deep breathing relaxation therapy and Qur’an recitation proved effective in reducing anxiety among hypertensive patients. This intervention is recommended as part of nursing management and can be consistently applied as an independent practice by patients.